Impact of Age, Experiences, Education, Working Hours, and Household Expenditure on Juju Dhau Traders’ Income in Bhaktapur Municipality - Adhikari, Padma Kumar; Dangal, Dil Nath; Lamichhane, Kul Prasad; Ghimire, Krishna Prasad (Economic Review of Nepal, 2025)
This study investigates the socio-economic dynamics of Juju Dhau traders' income in Bhaktapur Municipality. The research is based on primary data collected through field surveys conducted in December 2022 and January 2023, focusing on the impact of respondents' age, working experiences, education level, working hours, and household expenditure. The conclusion is based on ANCOVA regression techniques after utilizing home ownership and marital status as dummy-coded drivers. The regression analysis highlights a strong positive relationship between household expenditure and family income. Other relationships, however, require further investigation due to unexpected signs or lack of statistical significance. Marital status, further, influenced income-generating activities through its interaction with working hours and expenditure patterns, reflecting the complexities of family income dynamics in this traditional trade. To ensure the sustainability of Juju Dhau production and trade, the study recommends preserving its cultural significance while addressing challenges such as market limitations and competition from industrial dairy products. Additionally, it highlights the need for future research to explore the long-term effects of these variables on income stability and to investigate how integrating modern practices with traditional methods could enhance the economic resilience of traders in the Bhaktapur region.